1984
DOI: 10.1111/j.1471-4159.1984.tb06091.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analyses of Brain Synaptic Peptides Containing Taurine

Abstract: The structure of a number of low-molecular-weight acidic peptides containing taurine prepared from calf brain synaptosomes and their subcellular vesicles was studied using electron impact mass spectrometry. At least seven sequences could be identified: N-acetylaspartyl-glutamyl-taurine, N-acetylaspartyl-taurine, N-acetylglutamyl-taurine, glutamyl-taurine, aspartyl-taurine, seryl-glutamyl-seryl-taurine, and seryl-taurine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Taurine is often referred to as an amino acid and small polypeptides have been identified which contain taurine (Marnela et al . ). This incorporation remains, however, a mystery as no aminoacyl tRNA synthetase has been recognized as identifying taurine and capable of incorporating it into a tRNA (Lahdesmaki ).…”
Section: Taurine Biophysicsmentioning
confidence: 97%
“…Taurine is often referred to as an amino acid and small polypeptides have been identified which contain taurine (Marnela et al . ). This incorporation remains, however, a mystery as no aminoacyl tRNA synthetase has been recognized as identifying taurine and capable of incorporating it into a tRNA (Lahdesmaki ).…”
Section: Taurine Biophysicsmentioning
confidence: 97%
“…The synthetic stereoisomer y-D-glutamyltaurine is a potent antagonist of the quisqualate and kainate subtypes of the excitatory a.mino acid receptor and has been used in their characterization (161). Various acylated peptides have also been reported, such as N-acetylaspartylglutamyltaurine, N-acetylaspartyltaurine, and N-acetylglutamyltaurine (496). The study of taurine-containing peptides is still in the early stages.…”
Section: F Xenobiotic Conjugationmentioning
confidence: 99%
“…The present evidence that it can be isolated from mammalian brain gives some support to our previous suggestions that this peptide may be localized in neurons. Independently of the mass spectrometric data by the Finnish group (Marnela and Lahdesmaki, 1983;Marnela et al, 1984, we had found immunochemical and immunohistochemical evidence for the existence, in specific neurons in certain regions of rat brain, of taurine peptide(& most probably including or exclusively y-glutamyltaurine (Tomida et al, 1985;Ida et a]., 1987;Tomida and Kimura, 1987;Ienaga et al, 1988~-d). This evidence was based on work with antisera against taurine and y-glutamyltaurine in which it was found that each immunoreactivity (taurine-like and y-glutamyltaurine-like) was fundamentally different.…”
Section: Resultsmentioning
confidence: 98%